CRITICAL ANALYSIS OF FORMULAE FOR THE CALCULATION OF THE ELECTRICAL PARAMETERS OF HUMID MATERIAL - Zagirnyak Valentyna; Nevzlin Borys; Dziuban Vitaliy (Journal of Energy Technology, 2024)
A comparative analysis of conventional calculation expressions for the determination of the electric parameters of humid material has been done. Their disadvantages have been determined, and the errors of their use for calculation of electrical characteristics of a specific material (zinc cake) have been determined. A means of improving the considered calculation expressions has been proposed.